Nickel-Catalyzed Enantioselective Electrochemical Reductive Cross-Coupling of Aryl Aziridines with Alkenyl Bromides - Hu, Xia; Cheng-Sánchez, Iván; Cuesta-Galisteo, Sergio; Nevado, Cristina (ACS, 2023)
An electrochemically driven nickel-catalyzed enantioselective reductive cross-coupling of aryl aziridines with alkenyl bromides has been developed, affording enantioenriched β-aryl homoallylic amines with excellent E-selectivity. This electroreductive strategy proceeds in the absence of heterogeneous metal reductants and sacrificial anodes by employing constant current electrolysis in an undivided cell with triethylamine as a terminal reductant. The reaction features mild conditions, remarkable stereocontrol, broad substrate scope, and excellent functional group compatibility, which was illustrated by the late-stage functionalization of bioactive molecules. Mechanistic studies indicate that this transformation conforms with a stereoconvergent mechanism in which the aziridine is activated through a nucleophilic halide ring-opening process.
Keywords: Níquel; Aziridines; Cross-Coupling; Electrochemistry; Catalysis; Nickel